Evidence of Boron Assistance for CO2 Activation during Copper-Catalyzed Boracarboxylation of Vinyl Arenes: A Synthetic Model for Cooperative Fixation of CO2. Issue 4 (3rd July 2020) - Baughman, Notashia N.; Popp, Brian V.
ABSTRACT: In this comment, insights gained from density functional theory into the mechanism by which the Cu(I)-catalyzed boracarboxylation of vinyl arenes occurs with specific focus on the CO2 insertion step are presented. Preliminary calculations indicated a potential non-covalent interaction between boron and CO2 in the carboxylation transition state, implicating cooperative CO2 activation. A study of boron Lewis acidity was conducted through substitution of sp 2 mono-boron substituents. An inverse correlation between boron valence deficiency (BVD) and the enthalpic barrier of CO2 insertion into the β-borylbenzyl-Cu(I) bond was revealed, supporting Lewis acid/base cooperativity between boron and the proximal oxygen of CO2 at the carboxylation insertion transition state. These findings suggest that future methodology development should consider strategic incorporation of similar Lewis acidic functionality to facilitate carboxylation of challenging substrates. Graphical abstract: